CLIMATE AND ECOLOGY CHANGE IN ATMOSPHERE NORTH HEMISPHERE, INCLUDE ARCTIC, AFTER USING TACTIC NUCLEAR WEAPON - A. Е. Roshdestvensky (Модернизация, инновация, развитие, 2016)
In this particle the structure of large scale heat transport in atmosphere of north hemisphere are considered. The structure mention was calculated with using «shift phase method» in geostrophic approximation on based climate datum.The maps of heat transport structure, are presented in this article, contains the zone as sources of heat (heat ventilated zones), and heat bury zones (cool storage zones). In case of using tactic nuclear the global structure of mass and heat transport in atmosphere don't break and nuclear explosions may be considered only as indignation. If nuclear explosions are situated in heat ventilated zones, its ecological consequences are minimum, Contrary, when nuclear explosions are situated in heat bury zones, for example in some Arctic regions. Only two small regions in Arctic concerns to heat ventilated zones in atmosphere. This maps and results are allowed as protection to avoid the nuclear war (in any degrees), and simultaneously to vengeance for aggressor (for maximum damage with minimum efforts).